CONCENTRATED LOADS ON PLATES. - Nevel,Donald E. (1970)
An infinite plate on an elastic foundation is considered for a uniform load distributed over a circular area. The analysis of the problem is based on three-dimensional theory of elasticity. A numerical evaluation for the critical stress is made assuming a bending type of failure and the results closely agree with Westergaard's equations. (Author)